Manajemen Pembinaan Kemandirian Dan Kedisiplinan Santri Di Pondok Pesantren Al-Kasyaf Bandung - Rusmadi (ISLAMICA, 2022)
This study aims to analyze the implementation of the management of the independence and discipline of students at the Alkasyaf Islamic Boarding School in Bandung. This study uses a qualitative approach. While the method used is descriptive-analytical, they describe the implementation of punishment at the Alkasyaf Islamic Boarding School in Bandung. Based on the results of this study, it found that efforts to increase religion for students at Alkasyaf have been running and under management function procedures. There are still some shortcomings, while the drawback is that there is a lack of rest time for students because of the many activities at the Islamic boarding school, so the management applied is not realized. Maximally. In fostering student discipline, Al Kasyaf Islamic Boarding School applies the Reward and Punishment model, namely giving awards for positive things done by students and providing guidance with sanctions for negative things done. The students at the Alkasyaf Islamic Boarding School Apart from religious knowledge, the students are also equipped with other skills such as farming, writing, public speaking, and sewing as a form of life skills.